2023
DOI: 10.3390/ijms24065292
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Olive Oil and Extra-Virgin Olive Oil from Other Vegetable Oils by Targeted and Untargeted HRMS Profiling of Phenolic and Triterpenic Compounds Combined with Chemometrics

Abstract: Extra-virgin olive oil (EVOO) and virgin olive oil (VOO) are valuable natural products of great economic interest for their producing countries, and therefore, it is necessary to establish methods capable of proving the authenticity of these oils on the market. This work presents a methodology for the discrimination of olive oil and extra-virgin olive oil from other vegetable oils based on targeted and untargeted high-resolution mass spectrometry (HRMS) profiling of phenolic and triterpenic compounds coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…This leads to the conclusion that the differences between the different categories of olive oils, based on the evaluated parameters in the present study, do not allow us to clearly separate the two categories of EVOO and VOO oils. These findings are in agreement with those of a recent work [45] in which the authors indicated discrimination between EVOO and VOO and other vegetable oils, but no discrimination between EVOO and VOO was observed.…”
Section: Principal Component Analysissupporting
confidence: 93%
“…This leads to the conclusion that the differences between the different categories of olive oils, based on the evaluated parameters in the present study, do not allow us to clearly separate the two categories of EVOO and VOO oils. These findings are in agreement with those of a recent work [45] in which the authors indicated discrimination between EVOO and VOO and other vegetable oils, but no discrimination between EVOO and VOO was observed.…”
Section: Principal Component Analysissupporting
confidence: 93%
“…It is also interesting to consider the contribution of extra virgin olive oil to the phenolic composition of prepared bread, although to a lesser extent than wheat, since it accounts for 3% of the bread dough. In this sense, the presence of 3,4-dihydroxybenzoic acid, p-coumaric acid, trans-ferulic acid, and quercetin has been described in extra virgin olive oil marketed at concentrations lower than 0.46 µg•g −1 , while kaempferol was not detected [39], consistent with the results reported in Table 1. Overall, mandarin peel extracts were found to be more plentiful in phenolic compounds, with a total amount of 7 mg•g −1 of the polyphenols screened vs. 12.9 ± 0.3 µg•g −1 in the control bread, demonstrating their potential as a source of bioactive polyphenols to be used as functional ingredients in the development of enriched bread.…”
Section: Individual Phenolic Composition Of Mandarin Peel and Enriche...supporting
confidence: 89%
“…Hesperidin, rutin, and resveratrol appeared in a concentration range between 0.5 and 2 µg·g −1 . Coherent with the above results, phenolic acids have been reported to be more abundant than flavonoids in wheat, flour, and bakery products [ 3 ], as well as in extra virgin olive oil [ 39 ]. Ferulic acid accounted for more than 59% of the total phenolic acids in refined bread and whole bread, observing p -coumaric acid concentrations of 4.5 µg·g −1 [ 40 ].…”
Section: Resultsmentioning
confidence: 77%
“…As reported by Beltran et al (2021) [41], when olives are stored, the ethanol content increases inside the fruit, and this phenomenon is reflected in a deterioration in olive oil quality. It is worth noting that ethanol in olive fruit is one of the precursors of ethyl esters, which are a virgin olive oil quality parameter adopted recently by legislation to discriminate "extra virgin olive oil" produced from healthy and high-quality olive fruits [43]. This behavior was more restrained in the "Moraiolo" compared to the "Frantoio" olive fruits (Figure 3).…”
Section: Influence Of Olive Cultivar and Time Storage On Voc Emission...mentioning
confidence: 96%